A INFLUÊNCIA DA OBRA DE FREUD NA INTERPRETAÇÃO RICOEURIANA DO TRAÇO - Esteban Lythgoe (Eleuthería - Revista do Mestrado Profissional em Filosofia da UFMS, 2022)
Ricoeur made an important modification in his conception of history in History, Memory, Forgetting with respect to that of Time and Narrative. Instead of basing it on traces, it was founded on memory. In this article, we will begin by showing how this change have affected Ricoeur’s concept of history. Next, we will point out that these modifications were not the product of the memorial turn that occurred at that time, but the result of a long process. This included the convergence between history and psychoanalysis and stop basing the historian's debt to the past on the trace but on the testimony of the deaths